EFFECTIVENESS OF WILLIAM FLEXION EXERCISE TO REDUCE PAIN INTENSITY ON LOW BACK PAIN (LBP) OF WOODCARVERS IN BALI, INDONESIA - Istri Dalem Hana Yundari; Putu Puspita Wulandari Mas (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Previous study shown 8 of 10 woodcarver in Bali experience low back pain (LBP), a clinical syndrome with major symptoms of pain or discomfort sense in the lower back area. A William’s flexion exercise, an exercise program consisting of six kinds of movements, may decrease the pain by decreasing the lumbar lordosis (flexion). This study is to evaluate the effect of William’s Flexion Exercise in reducing pain intensity of LBP to woodcarvers in Bali, Indonesia.